Warrants and Their Underlying Stocks: Microstructure Evidence from an Emerging Market - Charoenwong, C. (Institutional Knowledge at Singapore Management University, 2012)
The Stock Exchange of Thailand (SET) provides an ideal platform for comparing the trading characteristics of warrants and their underlying stocks since both types of securities trade in the same market venue under identical trading rules. Hence, any impact of the trading protocol on the intraday variation of spread, depth, and order flow and on an informed trader’s decision to trade in warrants or stocks is naturally controlled. We find that the patterns of warrants and their underlying stocks are downward-sloping for spreads, U-shaped for flow toxicity, volatility, depth concentration, and trading volume, and upward-sloping for depth and market order flow ratio. This implies that trading under identical market structures leads to similar trading characteristics. We further document that flow toxicity is negatively related to spread and positively related to depth, market order flow ratio, trade size, trading value and volatility.